Developmental stability and environmental stress: A geometric morphometrics analysis of asymmetry in the human femur. Issue 1 (3rd September 2018) - Mopin, Clémence; Chaumoître, Kathia; Signoli, Michel; Adalian, Pascal
Abstract: Objectives: The evaluation of developmental stability (DS) by measuring fluctuating asymmetry (FA), a bioindicator of general cumulative stress, is an approach that has often been used to characterize health status in past populations. New techniques of geometric morphometrics now enable a better appreciation of FA than before, with a more refined quantification of variation. The aim of our study is to determine the effectiveness of geometric morphometrics analyses of asymmetry in the human femur for the study of individual DS and inferring health status of human populations. Materials and methods: We conducted a comparative analysis between two diachronic populations of distinct and known health status. Two samples of 70 pairs of adult femurs from individuals of comparable age range and sex were selected and CT‐scanned. For each 3D reconstruction, two sets of 27 landmarks were digitized to quantify and minimize the effect of measurement error on the evaluation of FA. Results: While the measurement of FA in femoral centroid size seemed comparable between the samples, the amount of FA in femoral shape differed. Individuals who experienced high levels of environmental stress presented higher intra‐individual variation. In parallel, results did not reveal any significant differences in DS between sexes or age groups. Discussion: The geometric morphometrics analysis of femoral asymmetry was effective for distinguishing two populations. After considering various factors of influence, genetics and biomechanics seem to have a limited impact on the results. Expressing FA appears to be normal but dependent on the disturbances of DS produced by environmental stress.